Preventing deaths due to haemorrhage. (October 2016) - Hofmeyr, G. Justus; Qureshi, Zahida
Abstract : Prevention of deaths from obstetric haemorrhage requires effective health systems including family planning, commodities, personnel, infrastructure and ultimately universal access to comprehensive obstetric care for women giving birth. The main causes of death associated with antepartum haemorrhage are placental abruption, placenta praevia and uterine rupture. Preventive measures include preconceptual folate supplementation, management of hypertensive disorders, early diagnosis of placenta praevia and use of uterine stimulants cautiously, particularly misoprostol. Preventive measures for post-partum haemorrhage include routine active management of the third stage of labour. Treatment involves a cascade of increasingly invasive interventions in rapid sequence until the bleeding is stopped. These interventions include fluid resuscitation, removal of the placenta, bimanual uterine compression, uterotonics, tranexamic acid, suturing of lower genital tract injury, blood product replacement, balloon tamponade, laparotomy, stepwise uterine devascularization, uterine compression sutures and hysterectomy. Emergency temporizing measures include application of the non-pneumatic anti-shock garment, and at laparotomy, aortic compression and uterine tourniquet application. The effectiveness of treatment methods and the optimal dosage of misoprostol are research priorities. Interesting new approaches include transvaginal uterine artery clamping and suction uterine tamponade. Highlights: Preventing deaths from obstetric haemorrhage requires effective health systems. The main causes of death associated with antepartum haemorrhage are placental abruption, placenta praevia and uterine rupture. Postpartum haemorrhage may be due to hypotonicity, retained products of conception or trauma affecting the uterus or lower genital tract. Treatment options should be continued in sequence until effective. Research priorities are effectiveness of treatment methods and optimal dosage of misoprostol.